The Economics of Artificial Intelligence 2019
DOI: 10.7208/chicago/9780226613475.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Its Implications for Income Distribution and Unemployment

Abstract: We would like to thank our discussant Tyler Cowan as well as Jayant Ray and participants at the NBER conference for helpful comments. We also acknowledge research assistance from Haaris Mateen as well as financial support from the Institute for New Economic Thinking (INET) and the Rewriting the Rules project at the Roosevelt Institute, supported by the Ford and Open Society Foundations, and the Bernard and Irene Schwartz Foundation. The views expressed herein are those of the authors and do not necessarily ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 27 publications
(31 reference statements)
0
45
0
8
Order By: Relevance
“…Poorly designed AI may further generate feedback loops that reinforce inequalities, as in the case of predictive policing (Kaufmann, Egbert, & Leese, 2019), for example, or in predictions of creditworthiness that render it difficult for individuals to escape vicious cycles of poverty (O’Neill, 2014). Indirectly harmful outcomes of AIs can arise from the application of AI technologies more generally, often with long-term consequences, such as large-scale technological unemployment (Korinek & Stiglitz, 2018). Such outcomes can also take the form of so-called latent, secondary, and transformative effects (Mittelstadt et al, 2016) that occur when AI outcomes change the ways that people perceive situations, as, for example, in the case of profiling algorithms that powerfully ontologize the world in particular ways and trigger new patterns of behavior (Pasquale, 2015), though these effects are also evident in the ways that content curation and news recommendation algorithms lead to people being unwittingly socialized in “filter bubbles” (Berman & Katona, 2020).…”
Section: Toward a Framework Of Responsibilities For The Innovation Of...mentioning
confidence: 99%
“…Poorly designed AI may further generate feedback loops that reinforce inequalities, as in the case of predictive policing (Kaufmann, Egbert, & Leese, 2019), for example, or in predictions of creditworthiness that render it difficult for individuals to escape vicious cycles of poverty (O’Neill, 2014). Indirectly harmful outcomes of AIs can arise from the application of AI technologies more generally, often with long-term consequences, such as large-scale technological unemployment (Korinek & Stiglitz, 2018). Such outcomes can also take the form of so-called latent, secondary, and transformative effects (Mittelstadt et al, 2016) that occur when AI outcomes change the ways that people perceive situations, as, for example, in the case of profiling algorithms that powerfully ontologize the world in particular ways and trigger new patterns of behavior (Pasquale, 2015), though these effects are also evident in the ways that content curation and news recommendation algorithms lead to people being unwittingly socialized in “filter bubbles” (Berman & Katona, 2020).…”
Section: Toward a Framework Of Responsibilities For The Innovation Of...mentioning
confidence: 99%
“…Therefore, the impact of AI on employment is expected to be stronger than that of the previous technological revolutions ( 10 ). AI is not only expected to replace jobs in the labor market but also to change the ways in which all occupations complete their tasks, leading to massive technology-driven unemployment in the future ( 11 , 12 ). Some scholars have found that empirically, industrial robots have had a greater impact than capital and other technological advances on the U.S. labor market, and the use of industrial robots has had a stronger negative impact on the employment-to-population ratio and the wage level in some U.S. industries ( 13 ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Acemoglu & Restrepo (2018a;2018b), Arntz et al (2017), valamint Autor & Salomons (2018) az automatizáció munkaerő-megtakarító jellegére, Autor et al (2003), Autor & Dorn (2013) és Michaels et al (2014) a munkaerőpiaci polarizáció jelenségére hívta fel a figyelmet. Az MI-re való átállás globális hatásai kapcsán, a témával szélesebb geoökonómiai perspektívában, a fejlett és fejlődő országok, illetve különböző munkaerőpiaci rétegek közötti egyenlőtlenséget növelő dinamikákkal foglalkozott Korinek & Stiglitz (2017, Aghion et al (2017) és Varian (2019).…”
Section: Szemléleti Keretekunclassified